Efficient ternary organic photovoltaic using polymers donor with two absorption peaks and similar HOMO levels as third component materials. (December 2022) - Man, J.; Liu, Z.
Abstract: The ternary strategy has been shown to be a promising approach to improve the performance of organic solar cells (OSCs). In this manuscript, the polymer donor Poly[N-9″-hepta-decanyl-2, 7-carbazole-alt-5, 5-(40, 70-di-2-thienyl-20, 10, 30-benzothiadiazole) (PCDTBT) was doped into a D18-Cl:Y6 binary film to fabricate ternary OSCs. PCDTBT has efficient short wavelength light absorption, appropriate content of PCDTBT yielded complementary absorption spectra, and good compatibility with the D18-Cl:Y6 binary films. In addition, the lower lowest unoccupied molecular orbital levels of PCDTBT than D18-Cl allow efficient exciton dissociation and reduce charge carrier recombination within the ternary film. The optimized ternary film has a more suitable phase separation scale, smooth surface, and higher crystallinity than D18-Cl:Y6 binary films. Therefore, the appropriate content of PCDTBT as the third component material can significantly enhance the short-circuit current density ( J SC ) and photovoltaic performance. The results show that ternary OSCs with both D18-Cl and PCDTBT donors can achieve high performance by well-optimized light absorption, exciton dissociation, and phase separation. Highlights: Ternary organic solar cells are fabricated with PCDTBT as third component materials. The improvement of charge dynamics process by ternary strategy. The improved energy transfer between PTQ10 and PCDTBT. The ternary organic solar cells with blend donor achieved a power conversion efficiency of 15.68%.